Relación entre la motivación de logro académico, la autoeficacia y la disposición para la realización de una tesis - Ruiz Dodobara, Fernando Gabriel (2005)
This paper is the report of a study about the problems which psychology students have to resolve when they write a thesis for obtaining the degree. In the frame of this study three variables were considered: academic achievement motivation, selfevaluated autoefficacy for writing a thesis, and the will to write her. A sample of´psychology students in the last academic semesters of three privates universities answered the psychometric reactives used for this study. The author comments the relationships between the variables and their intensity.